Islamic Entrepreneurship Education Model as An Empowerment Concept For Islamic Boarding Schools In Indonesia - Warda, Warda; Adiningrat, Andi Arifwangsa; Rizky, Muhammad; Haliding, Safri; Alamsyah, Alamsyah; Jusriadi, Edi; Agustan, Agustan; Akhmad, Akhmad (International Journal of Sharia Business Management, 2024)
Islamic boarding schools are Islamic educational institutions that are growing and expanding in society. Institutionally, Islamic boarding schools have potential and opportunities to be developed and empowered. In fact, many of their graduates are unemployed and cannot compete in society. This research aims to determine the Islamic entrepreneurship education model as a concept for empowering Islamic boarding schools. Background problem: Previously studied Mostly focused on General entrepreneurship education at the boarding school This Islamic boarding school is not optimal in increasing interest and culture student entrepreneurship in Islamic boarding schools. Novelty: The current study fills a gap, namely the inconsistencies of previous studies address problems directly, interest and increase the culture of entrepreneurship as an empowerment concept in Islamic boarding schools in increasing entrepreneurship and independence. Method study: Method used in this research qualitative methods. The data collected is analyzed systematically qualitatively using Miles and Huberman's interactive model. Activity in data analysis, namely data reduction, data display and conclusion drawing/verification. Findings/Results: The Islamic Entrepreneurship Education Model reveals that the scope of Islamic entrepreneurship education must include four criteria First character. Second Draft. Third Skills. Empowerment concept includes; identify business potential, capital capacity, and improvements management of Islamic boarding schools. Conclusion Research findings shows the Islamic entrepreneurship education model as an empowerment concept in Islamic boarding schools can increase interest, independence and entrepreneurial culture